Beta-Thalassemia with Initial Presentation as Immune Thrombocytopenia: A Case Report - Hyun Sik Kang (The Korean Society of Pediatric Hematology-Oncology, 2023)
Immune thrombocytopenia (ITP) is characterized by a low platelet count caused by immune-mediated platelet destruction. In children, ITP usually resolves on its own within three months, but treatment may be necessary in some cases. Beta-thalassemia (BT) is an inherited anemia caused by a deficiency in beta-globin protein chain synthesis, and its prevalence is increasing worldwide. Anemia is the most critical symptom, and its severity varies from mild to severe. Patients with BT typically have normal white blood cell (WBC) and platelet counts; however, in some cases, they may experience thrombocytosis or thromboembolic events. Thrombocytopenia is rare in patients with BT; however, some cases of ITP and BT co-occurrence have been reported in patients with thrombotic thrombocytopenic purpura (TTP). This report describes the case of a five-year-old girl diagnosed with BT who presented with immune thrombocytopenia and received rituximab.